Identifying Redox-Sensitive Cysteine Residues in Mitochondria - Eleni A. Kisty; Emma C. Saart; Eranthie Weerapana (MDPI AG, 2023)
The mitochondrion is the primary energy generator of a cell and is a central player in cellular redox regulation. Mitochondrial reactive oxygen species (mtROS) are the natural byproducts of cellular respiration that are critical for the redox signaling events that regulate a cell's metabolism. These redox signaling pathways primarily rely on the reversible oxidation of the cysteine residues on mitochondrial proteins. Several key sites of this cysteine oxidation on mitochondrial proteins have been identified and shown to modulate downstream signaling pathways. To further our understanding of mitochondrial cysteine oxidation and to identify uncharacterized redox-sensitive cysteines, we coupled mitochondrial enrichment with redox proteomics. Briefly, differential centrifugation methods were used to enrich for mitochondria. These purified mitochondria were subjected to both exogenous and endogenous ROS treatments and analyzed by two redox proteomics methods. A competitive cysteine-reactive profiling strategy, termed isoTOP-ABPP, enabled the ranking of the cysteines by their redox sensitivity, due to a loss of reactivity induced by cysteine oxidation. A modified OxICAT method enabled a quantification of the percentage of reversible cysteine oxidation. Initially, we assessed the cysteine oxidation upon treatment with a range of exogenous hydrogen peroxide concentrations, which allowed us to differentiate the mitochondrial cysteines by their susceptibility to oxidation. We then analyzed the cysteine oxidation upon inducing reactive oxygen species generation via the inhibition of the electron transport chain. Together, these methods identified the mitochondrial cysteines that were sensitive to endogenous and exogenous ROS, including several previously known redox-regulated cysteines and uncharacterized cysteines on diverse mitochondrial proteins.